2012
DOI: 10.1080/00380768.2012.664783
|View full text |Cite
|
Sign up to set email alerts
|

Net and gross nitrification in tea soils of varying productivity and their adjacent forest and vegetable soils

Abstract: Tea (Camellia sinensis (L.) O. Kuntze) is a globally important crop and is unusual because it both requires and acidifies the soil in which it grows. In spite of the low pH, high nitrate (NO À 3 ) accumulates in tea soils, resulting in a great potential for diffuse pollution. Nitrification in tea soils remains poorly understood. The purpose of this study was to investigate net and gross nitrification in three tea soils with varying productivity, their adjacent forest and vegetable soils. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…However, the opposite results were also found in Yiwu and Jiangshan farms with conventional fields having significantly higher nitrification rates (Table 5). This is probably because the chemically N fertilized soils have a higher nitrification substrate, nitrifying activity and an accelerated growth of the nitrifying population (Chu et al 2008;Gong et al 2011;Han et al 2012). In this study, we found these two farms had higher initial NH 4 + -N compared to other sites, and the initial NH 4 + -N concentration was significantly correlated with the nitrification rate (r = 0.683, n = 11, p < 0.05).…”
Section: Soil Microbial Biomass Size and Microbial Activitiessupporting
confidence: 60%
“…However, the opposite results were also found in Yiwu and Jiangshan farms with conventional fields having significantly higher nitrification rates (Table 5). This is probably because the chemically N fertilized soils have a higher nitrification substrate, nitrifying activity and an accelerated growth of the nitrifying population (Chu et al 2008;Gong et al 2011;Han et al 2012). In this study, we found these two farms had higher initial NH 4 + -N compared to other sites, and the initial NH 4 + -N concentration was significantly correlated with the nitrification rate (r = 0.683, n = 11, p < 0.05).…”
Section: Soil Microbial Biomass Size and Microbial Activitiessupporting
confidence: 60%
“…However, when forestlands are converted to agricultural lands, nitrification is stimulated and microbial immobilization of NO 3 − is substantially suppressed (Yang et al, 2008;Zhang et al, 2013a). Therefore, NO 3 − dominance in inorganic N in agricultural soils and the mechanism of N retention in humid subtropical soils is destroyed (Yang et al, 2010;Han et al, 2012;Zhang et al, 2013a). It has been observed that management practices, such as fertilization, stimulate the activity of nitrifying bacteria (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have well reported the cycle of individual elements, such as Al (Flaten 2002), N (Han et al 2012) and P (Debnath et al 2011) in tea plantations, which were generally tested by our study. However, we know little about at what points the major biogeochemical cycles interact and how these linkages are affected by environmental change and fertilization management and the development of tea plantations (Marklein and Houlton 2012).…”
Section: Discussionmentioning
confidence: 67%
“…Currently, there are 3 million ha of tea plantations, globally (Xue et al 2013). In subtropical China, most of the tea-growing areas are acidic-leached red soil (Ultisols) with poor amounts of available nutrients (Han et al 2007;Debnath et al 2011;Han et al 2012). And soil Al availability, in forms such as soluble Al, exchangeable Al and organic Al complexes, has increased with an increased acidic environment in this area.…”
Section: Introductionmentioning
confidence: 99%